Practical Performance Evaluation of Maximum Power Point Tracking Algorithms in a Photovoltaic System - Hassan Abouobaida; EL Beid Said (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper addresses a performance evaluation of maximum power point tracking techniques (MPPT) in a photovoltaic system. This research work finds its applications in photovoltaic systems producing electric power with a better energy efficiency, which will lead to an improved relationship between the cost and the amount of the produced power. The importance of this work resides on the one hand in the evaluation of the performances of the different MPPTs according to three criteria instead of one or two criteria in other works of the literature and on the other hand in the study of Four algorithms in one paper and their comparisons. This paper discusses the performance evaluation of the MPPT algorithms called P&O, Inc-Cond, Hill-Climbing and Fuzzy algorithms based simulation results and practical validation. The performances of these algorithms are evaluated according to the following criteria: The response time, the amplitude of the oscillations around the optimal point and the accuracy. The objectives in this article are summarized in the following points: (a) modeling the photovoltaic systems, (b) presenting and detailing each MPPT algorithm (c) presenting and discussing the simulation results in Matlab/Simulink and practical validation (d) evaluating the performance of each algorithm. This paper is completed by a summary on the areas of use for each algorithm and conclusions.